1996
DOI: 10.1002/(sici)1097-0029(19961101)35:4<340::aid-jemt5>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Participation of endodermal epithelial cells on the synthesis of plasma LDL and HDL in the chick yolk sac

Abstract: We ultrastructually examined the chick yolk sac endodermal epithelium and evaluated our findings in combination with the biochemical analysis of serum and yolk lipoproteins. Twenty‐five to 30 nm‐sized particles were demonstrated to be a principal element of the extracellular yolk mass and these were determined to be yolk very low density lipoprotein (VLDL). The particles were shown to be taken up by the epithelial cells via coated pits and engulfed by plasma membrane invaginations together with yolk subdroplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…lipoproteins) for targeting to the embryo. Although a participation of the YS EECs in the synthesis of lipoproteins has been implied previously (35), proteins required for lipoprotein production…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…lipoproteins) for targeting to the embryo. Although a participation of the YS EECs in the synthesis of lipoproteins has been implied previously (35), proteins required for lipoprotein production…”
Section: Resultssupporting
confidence: 66%
“…Furthermore, in functional terms, this finding complements data from electron microscopy studies showing that the EECs from the area vasculosa, but not from the area vitellina, contain numerous coated pits and canaliculi at their apical plasma membrane (8). Recently, based on gene expression profiling (9) and ultrastructural studies (35), secretion of serum proteins and lipoproteins by the chicken YS endoderm has been proposed but was not analyzed by biochemical means. Studies by Farese et al (47), using embryonic-lethal apoB knock-out mice, concluded that apoB plays an essential role in the transport of lipids via secretion of apoB-containing lipoproteins; however, again, lipoprotein synthesis and secretion were not documented by direct evidence.…”
Section: Discussionmentioning
confidence: 99%
“…The yolk sac has previously been implicated as the major source of lipoproteins and, in particular, the site of cholesterol esterification, in the embryonic circulation (4, 33, 47). However, studies on the biosynthetic capacity of EECs have not addressed the composition and nature of the protein moieties of secreted lipoproteins (27,48). Previous studies have reported the presence of apoB mRNA in yolk sac (49).…”
Section: Discussionmentioning
confidence: 99%
“…The results described in the present study may help to define the biochemical processes that link the absorptive events at the apical surface with the subsequent secretory events at the basal surface of the endodermal cells. There is evidence that, as a result of fusion with lysosomes, the large lipid-rich vacuoles formed by the phagocytotic process are converted to socalled lipolysosomes in which the hydrolysis of the vacuolar contents proceeds at a high rate, catalyzed by lysosomal lipases and proteases (32). We propose that the products of this hydrolysis (free fatty acids, partial glycerides, glycerol, free cholesterol, lyso-PL, and the like) diffuse out of the large vacuoles and are transported to the endoplasmic reticulum where reesterification to synthesize TAG, PL, and CE is rapidly achieved by the very high activities of MGAT, GPAT, DGAT, acyl-CoA:acyltransferase, and presumably of the other enzymes required for complex lipid synthesis.…”
Section: Discussionmentioning
confidence: 96%